African Development Indicators 2000 (the international bank for reconstruction and development, 2000)
Each new volume provides access to more focused information, and represents an improvement in the quality, and availability of the data. The data contained in this report stems mostly, from national statistical services in Africa, and, additionally, many international agencies compile data on Africa, presented in a standardized framework. World Bank staff, supplement estimates to help address missing, or inconsistent data from standard sources, and, these differences in methodologies are addressed throughout in chapter introductions, and in technical notes.